A spontaneous binge-like eating model in mice using unpredictable once weekly access to palatable diets. (1st July 2018) - Murphy, Michelle; Dijkstra, Dorieka J.; Duncan, Jacqueline S.; Horgan, Graham W.; Mercer, Julian G.
Abstract: Many pre-clinical models of binge-like eating involve predictable, scheduled, access to a palatable diet high in fat (HF), where access may be preceded by anticipatory behaviour. Here, to introduce spontaneity into the binge-type consumption of palatable diets, mice were allowed 2 h access on a random day once per week and at a random time within an 8 h window either side of the transition from dark phase to light phase. Despite normal intake of a stock diet prior to unpredictable access to HF diet, mice immediately initiated a substantial eating episode when presented with HF diet. Following this consumption, compensatory hypophagia was observed relative to stock diet-fed controls, and cumulative energy intakes converged. There were no effects of HF diet on body weight or body composition over a 12-week period. Binge-like consumption was also observed on unpredictable access to the complete liquid diet, chocolate Ensure, but not with a 10% sucrose solution. Binge-like responses to unpredictable access to HF diet or Ensure were similar in male and female mice, although there were effects of sex on caloric consumption from stock diet in the compensatory period following palatable diet intake, with higher intakes in females. The timing of the 2h access period relative to light phase transition affected intake of palatable diets, but less robustly than the equivalent effect on stock diet intake during the same timed periods – the diurnal patterning of energy intake was diet sensitive. The large spontaneous binge-like consumption on unpredictable access to either solid or liquid palatable diets in mice of either sex offers the potential to combine these attributes with other manipulations where a developing obesity is part of the binge-like eating phenotype.